Lo sviluppo professionale docente dalle competenze alla capacitazione Un modello per la prescolastica - Urbani, Chiara (FrancoAngeli, 2018)
"With the evolution of today's educational contexts, teacher education is becoming increasingly important into European political discussion, in relation to its ability to improve the results of student learning. The need to confront new changes clearly signifies that the professionalism of teachers cannot be limited to competencies and skills learning, however, it does require new strategic dimensions of professional activation, oriented towards better identifying personal goals and strategies to be achieved. The text re-draws the paradigm of the continuing teacher professional development by integrating the capability approach with the models of competencies. Starting from the analysis of European policies on teacher education, the text carry out an experimental research into pre-school settings to explore the importance of individual choice: throught the creation of innovative research tools and a self-training methodology, pre-school teachers involved improved their self-determine agency and better qualified professional development. The text meets the interests of researchers, as a important contribution to rethink the topic of teacher training, also for the chosen methodological approach; for teachers, it wants to deepen the sense of educational professionalism, updated to the most recent topics and issues; finally, it meets the interests of aspiring in-training teachers or aspiring researchers for the richness of its contents, in order to inspire the elaboration of new, original research perspectives."